Hours Meter Report System Application for Heavy Equipment at PT. Belawan Indah - Setiawa, Dimas Putra; Hasdiana, Hasdiana; Irwan, Dedy (Al'Adzkiya, 2021)
Crane (heavy equipment) is one of the tools to unload and load containers from ships / depots. Because of its very important uses, each component of the crane must be checked every day before and after use. To improve the efficiency of the reporting process, an information system or additional feature is created which can be used by technicians in reporting cranes. The technology used in the form of Android-based applications so that it can be accessed mobile by anyone, anywhere, and anytime. This system uses the Waterfall method, the Waterfall Method is used aims to develop a system of crane usage reports, which is carried out sequentially or linearly. The system is made as easy and simple as possible so that the operator does not have trouble inputting reports. This system will provide information reports to Bosses / Pic who can monitor the condition of the crane only through logins to the system or sent emails. With this system all information will be captured clearly and neatly in accordance with the SOP in the company. Keyword : Heavy Equipment Crane, Android, Waterfall, Information System